PENGARUH PEMBELAJARAN AKTIF TIPE COLLABORATIVE LEARNING GROUPS TERHADAP PEMAHAMAN KONSEP DAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII SMPN DI KECAMATAN LEMBAH GUMANTI - NURLEV AVANA (Jurnal Muara Pendidikan, 2018)
The ability of understanding mathematical concepts and communication skills was a math learning goals stated by the Ministry of Education, and was a very important aspect in learning mathematics. Lack of communication skills and understanding of mathematical concepts students will affect the quality of student learning that result in low student achievement in school, it was also happening in SMP N Lembah Gumanti. Coperative learning group learning strategies was one alternative to improve the liveliness and creativity of students in learning. This research is a Quasi Experiment. The population in this study were students of SMP N Lembah Gumanti District. The samples in this study were students of class VIII 2 SMPN 2 Lembah Gumanti as experimental class and VIII A SMPN 1 grade students as a class randomly selected controls. Instrument used was a written test. The data obtained were analyzed using test mann- whitney u. The results showed that the ability of understanding the overall concept and capable students who are taught by low initial learning activen learning higher than students taught with conventional learning, communication skills and capable overall high initial learning strategies taught by ctiven learning higher than the students who taught by conventional learning.